Roles of Non-Coding RNAs in Primary Biliary Cholangitis - Zhang, Yaqin; Jiao, Ziying; Chen, Mingwei; Shen, Bing; Shuai, Zongwen (Frontiers in Molecular Biosciences, 2022)
Primary biliary cholangitis (PBC) is an autoimmune-mediated chronic cholestatic liver disease, fatigue and skin itching are the most common clinical symptoms. Its main pathological feature is the progressive damage and destruction of bile duct epithelial cells. Non-coding RNA (NcRNA) mainly includes microRNA (miRNA), long non-coding RNA (lncRNA) and circular RNA (circRNA), which are significant regulators in distinct physiological and pathophysiological processes. Accumulating studies have implicated the critical role of ncRNAs in inflammation and autoimmune regulation. Many validated ncRNAs have been identified as promising biomarkers for the diagnosis and treatment of PBC. This review will shed some light on PBC pathogenesis and be helpful for identifying potential ncRNA biomarkers for PBC.